THE EFFECTIVENESS OF UTILIZING INTERACTIVE METHODS AND DIGITAL TOOLS IN TEACHING ENGLISH IN EDUCATIONAL INSTITUTIONS (International Conference on Modern Science and Scientific Studies, 2025)
This article examines the effectiveness of implementing modern interactive teaching methods in English language instruction, with a particular emphasis on digital tools and brainstorming strategies. In the context of globalization, the number of learners acquiring English as a second language is steadily increasing. Therefore, it is essential to organize the educational process in a more student-centered, interactive, and efficient manner.Alongside traditional approaches, the integration of contemporary information and communication technologies (ICTs) — particularly interactive platforms such as Quizlet and Wordwall — has proven to be effective in fostering learners’ vocabulary acquisition, engagement, and autonomy. These tools enable educators to design customized learning experiences that respond to diverse student needs, ultimately enhancing learning motivation and outcomes.Furthermore, the application of the brainstorming technique significantly contributes to the development of students’ independent thinking, creativity, and communication skills. By encouraging the free exchange of ideas and active participation, brainstorming nurtures critical thinking and improves learners’ ability to articulate thoughts in English.This paper highlights the pedagogical value and practical implications of these tools and methods, demonstrating their positive impact on the quality of English language education. The findings suggest that the effective combination of digital technologies and interactive methodologies can create a dynamic learning environment that meets the needs of 21st-century learners.